(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study to describe the clinical, paraclinical characteristics and evaluate the treatment outcomes of influenza A in children under 5 years of age treated at the pediatric department in Hai Duong General Hospital. Subjects: 40 children were diagnosed with influenza A and treated at the pediatric department in Hai Duong General Hospital from January 2025 to October 2025. Methods: A retrospective and prospective, cross-sectional descriptive. Results: the mean age of the study population was 34.2 ± 5.8 months, children aged from 12 to under 60 months were the most common, the male/female ratio was 1.86/1. The common clinical manifestation were fever (97.5%), cough (95%), and rhinorrhea (65%). Other symptoms such as headache, sore throat, myalgia, abdominal pain, vomiting were less common. The paraclinical showed that 50% of patients had leukocytosis and 15% had leukopenia, 55% of patients did not exhibit elevated CRP levels (<10 mg/L). The succeedly cured result was 100%. The averaged hospital-stayed period were 6.4 ± 2.4 days. Conclusion: Children aged 12 to under 60 months were the most commonly affected age group among patients with influenza A. Clinical, paraclinical characteristics were generally non-specific. The most frequent complications were pneumonia and bronchitis. The mean treatment duration was 6.4 ± 2.4 days. Close monitoring of disease progression and early detection of complications are essential for timely management and to reduce treatment duration.